Experimental investigation of supercavitating flows - Byoung-Kwon Ahn (International Journal of Naval Architecture and Ocean Engineering, 2012)
When the object is traveling in the water at tremendously high speeds, the cavity forms and grows up at a fore part of the object called cavitator, and the object is eventually enveloped by vaporized water, supercavitation. As a result, the only part of the object in direct contact with the water is the cavitator, so skin-friction drag is significantly reduced. This is why recently supercavitating objects have been interested in many applicable fields. In this study we are focused out attention on supercavitating flows around various shapes of two and three dimensional cavitators. First, general features of supercavitation are examined by analyzing results obtained by the previously developed numerical method. Second, experimental observations are carried out at a cavitation tunnel at the Chungnam National University (CNU CT), and supercavity dimensions are scrutinized.